'I once wore an angry bird T-shirt and went to read Qur'an': Asymmetrical institutional complexity and emerging consumption practices in Pakistan. (September 2019) - Husain, Saima; Molesworth, Mike; Grigore, Georgiana
This article brings together theories of institutional logics and the exploration of the lives of tweens in Pakistan to understand how emerging consumption practices fit within Pakistani children's daily lives, and how institutional complexity that includes the dominance of religion under Pakistani Islamization is negotiated to separate and maintain the differences between them. We identify resolutions to asymmetrical institutional complexity in the consumption of character T-shirts: spatial–temporal practices, visual practices, symbolic substitution practices and single logic practices. We contribute to an understanding of how consumption happens in an Eastern Muslim culture, and how multiple institutional logics shape the consumption practices of children, by articulating how halal consumption practices, far from being essentialist, or presented as market segmentation, form from negotiations and reflections at the boundaries where Islam and Market logics meet.